OCORRÊNCIA DE INOVAÇÕES NA CONSTRUÇÃO CIVIL: ESTUDO DE CASO EM OBRA NO MUNICÍPIO DE ASSU/RN - Morais, Eduardo F.; Barreto, Aerson M.; Eduardo, Antunes F.; Bertini, Alexandre A. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Brazilian civil construction industry has been steadily improving its technological innovations. The taboo of traditionalism very common in civil construction has been broken through new work methodologies, new forms of management, specialization of labor, new equipment and materials. This work will address a technological innovation made by the workers themselves in a housing project in the city of Assu/ RN, the mortar tipping stand. In order to avoid waste of material and optimize working time, thus generating savings, the mortar regularizer was developed, it standardizes the amount of mortar that will be inserted under the septa of the structural blocks. Practical accompaniment of this innovation was carried out and informal questions were asked to the workers of three different works, including the housing set that created the innovation studied, to know their opinion and improvement and / or difficulties that on their workability with the equipment.